Mesostructuring layered materials: self-supported mesoporous layered double hydroxide nanotubes. Issue 27 (22nd June 2021) - Morais, Alysson F.; Nanclares, Dimy; Silva, Ivan G. N.; Duarte, Alfredo; Garcia, Fernando A.; Breynaert, Eric; Mustafa, Danilo
Abstract : Incorporation of Eu 3+ in the hydroxide layers of layered double hydroxides (LDH) enables the curvature of the LDH sheets, allowing the self-assembly of high surface area LDH nanotubes through a facile soft-templating strategy. Abstract : Synthesis of layered materials exhibiting hierarchical porosity remains challenging, but nevertheless worthwhile because it turns such solids into functional materials with high specific surface area. Using a soft-templating strategy in combination with the incorporation of 8-fold coordinated Eu 3+, self-assembly of self-supported layered double hydroxide (LDH) nanotubes has been achieved. Heteromorphic equimolar substitution of Al 3+ by Eu 3+ in Zn 2+ /Al 3+ LDH solids intercalated with 1, 3, 5-benzenetricarboxylate anions (BTC) assists precipitation of the double hydroxide layers onto the convex surface of Pluronic® P-123 worm-like micelles, yielding multilayer cylinders of BTC-intercalated LDHs. Removal of the micellar template is easily achieved by liquid extraction with methanol, yielding a network of interconnected, well-defined, self-supported, multi-walled, hollow cylindrical nanotubes. Removal of Eu 3+ from the synthesis disables formation of the nanotubular morphology, but still yields LDHs containing a network of embedded mesopores, resulting in a specific surface area that is 5-fold higher as compared to standard LDHs.